PENYELENGGARAAN PEMERINTAHAN DESA DI INDONESIA BERDASARKANUU No. 32TAHUN 2004 TENTANG PEMERINTAHAN DAERAH - Yusdianto Yusdianto (Universitas Lampung, 2007)
Under the provisions of Law No. 32 of 2004, the Village is a community unit either by law or by customary law which occupies a territory, led by a village chief and aided by some people as helpers to carry out the administration of the village. Village Government consists of Village Administration and Village Consultative Body (BPD), which serves the village with the rules set village head, accommodate and channel the aspirations of the people. Rural finance encompasses all the rights and obligations of the village which can be valued in money and everything in cash or goods that can be owned by the village related to the implementation of rights and obligations. Cooperation between villages and villages with third parties carried out in accordance with the authority of the village by the legislation.Keywords Village Government, Law 32 of 2004